Comparative Pharmacokinetics and Bioequivalence Evaluation of Two Formulations of Pramipexole Dihydrochloride Extended-Release Tablets in Healthy Chinese Subjects Under Fasted and Fed States: A Randomized, Open-Label, Single-Dose, Two-Period Crossover Clinical Trial - Yang L; Zhang L; Luo Z (Drug Design, Development and Therapy, 2023)
Ling Yang,1,2,* Liangliang Zhang,3,* Zhu Luo2 1Department of Neurology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Clinical Trial Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, West China Hospital, Sichuan University, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhu Luo, Clinical Trial Center, West China Hospital, Sichuan University, No. 37 Guoxue Lane, Chengdu, Sichuan, 610044, People’s Republic of China, Tel +86 028 85422707, Email luozhu720@163.comBackground: Pramipexole dihydrochloride extended-release tablet is a novel long-acting form of non-ergot dopamine agonist indicated as one of main therapeutic approaches for Parkinson’s disease. However, pharmacokinetic properties of extended-release pramipexole in healthy Chinese subjects remain unclear.Methods: A single-center, randomized, open-label, two-period crossover, single-dose study was performed to investigate comparative pharmacokinetics and evaluate bioequivalence of 0.375 mg test (Yangtze River Pharmaceutical Group Co., Ltd.) and reference (Trade name: Sifrol®, Boehringer Ingelheim Pharma GmbH & Co. KG) formulations of pramipexole dihydrochloride extended-release tablets in healthy Chinese subjects under fasted and fed states.Results: A total of 56 subjects (28 in each dietary trial) were enrolled and randomized. After single dose of 0.375 mg test and reference formulations under fasted condition, main pharmacokinetics of pramipexole were as follows: peak concentration (Cmax) were 409.33± 95.93 and 413.77± 132.03 pg/mL; plasma area under concentration–time curve from time 0 to last measurable concentration (AUC0-t) were 8801.95± 1966.83 and 8646.37± 2600.49 h*pg/mL; AUC from time 0 to infinity (AUC0-∞) were 9469.03± 1991.61 and 9082.95± 2666.26 h*pg/mL; elimination half-life (t1/2) were 11.98± 3.91 and 9.85± 2.63 h; both time to reach Cmax (Tmax) were about 4.50 h, respectively, for test and reference formulations. The 90% confidence intervals of geometric mean ratios (test/reference) of Cmax, AUC0-t and AUC0-∞ under fasted and fed conditions were all within 80– 125%. Following administration under fed condition, Cmax and Tmax for both test and reference formulations slightly increased and prolonged to 5.0 h, respectively, but AUC approximately remained unchanged compared with dosing under fasted condition. Test and reference formulations showed similar bioequivalence and favorable safety under fasted and fed states.Conclusion: Test and reference formulations of pramipexole dihydrochloride extended-release tablets (0.375 mg) showed similar bioequivalence and well safety and tolerability in healthy Chinese subjects under fasted and fed states, which supports further investigations of test formulation in patients with Parkinson’s disease.Keywords: pramipexole dihydrochloride extended-release tablet, bioequivalence, pharmacokinetics, safety, Parkinson’s disease